Bangladesh politics, economics, and civil society - Lewis, David 1960- (Cambridge University Press, 2011)
Since its hard-won independence from Pakistan, Bangladesh has been ravaged by economic and environmental disasters. Only recently has the country begun to emerge as a fragile, but functioning, parliamentary democracy. The story of Bangladesh, told through the pages of this concise and readable book, is a truly remarkable one. By delving into its past, and through an analysis of the economic, political and social changes that have taken place over the last twenty years, the book explains how Bangladesh is becoming of increasing interest to the international community as a portal into some of the key issues of our age. In this way the book offers an important corrective to the view of Bangladesh as a failed state
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Politik; Wirtschaft; Landeskunde; Gesellschaft; Bangladesh / Politics and government / 1971-; Bangladesh / Economic conditions; Bangladesh / Social conditions; Bangladesch